Madrasah Unggulan Berbasis Pesantren - Siswanto Siswanto (Ulumuna, 2014)
In the context of rapid social changes, can be considered alternative and outstanding Indonesian Islamic education institution. This article is aimed at analyzing opportunities and threats faced in the development of the madrasah, especially, those are located in pesantren, and so called pesantren-based madrasah. It is recommended that the development of pesantren-based madrasah have to fit the criteria of alternative education. It must be directed toward the creation of excellent and competitive Islamic school that will produce qualified human resources, who master not only religion but also science and technology inspired by Islamic values. Pesantren has become a center of excellence for human resources development that emphasizes morality for society development. Thus, the idea to realize a high-ranking madrasa in the boarding school is directed toward the integration of excellent intellectualism and skill with the excellent religious knowledge, including the excellence of personality, faith and piety.